Drawing Drawings: Toward a Narrative Architecture - Clear, Nic (Architecture Image Studies, 2020)
This introductory article opens the subject matter of the second issue of AIS, Narrative Architecture. Drawings have always contained the possibility of being more radical than the architecture they represent. Given the status of architecture within the current building industry, architecture needs to be oppositional to the values of laissez-faire capitalism and its environmentally catastrophic consequences. In many ways, the development of digital forms of representation has freed the architectural drawing from its historic association with its role as a vector for traditional forms of building. Architects no longer need to make drawings for buildings, but now have the opportunity to make drawings for other things.